2007
DOI: 10.1002/pbc.20803
|View full text |Cite
|
Sign up to set email alerts
|

MGMT promoter methylation correlates with survival benefit and sensitivity to temozolomide in pediatric glioblastoma

Abstract: As in adults, pediatric GBM patients with methylated MGMT promoter benefited from temozolomide. However, a stronger correlation with overall survival, regardless of treatment, was observed in this group of patients. These data suggest that MGMT methylation may be a prognostic factor for survival in pediatric GBM, as well as a marker for temozolomide sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
103
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(106 citation statements)
references
References 16 publications
0
103
0
1
Order By: Relevance
“…The expression level of MGMT is also susceptible to epigenetic silencing (46). Although our data showed that TMZ/ PYR treatment induced more DNA damage through the formation of DSBs (Fig.…”
Section: Discussionmentioning
confidence: 60%
“…The expression level of MGMT is also susceptible to epigenetic silencing (46). Although our data showed that TMZ/ PYR treatment induced more DNA damage through the formation of DSBs (Fig.…”
Section: Discussionmentioning
confidence: 60%
“…In certain cell lines, an enhancement of the radiation effect has been demonstrated, whereas other cell lines have shown no interaction, but merely an additive effect (78)(79)(80)(81)(82)(83).…”
Section: Temozolomidementioning
confidence: 99%
“…For example, a study using commercially available anti-MGMT antibodies to determine MGMT expression reported major interobserver variability (9,14). Furthermore, as MGMT promoter methylation is inversely correlated with MGMT expression (5,6), methylation-specific PCR (MSP) with bisulfate-treated DNA has been widely used to analyze MGMT promoter methylation status (7)(8)(9). However, MSP is only able to detect a limited number of methylated CpG sites in the primer region, and recent studies report that the region commonly investigated by MSP does not cover CpG sites that are most highly associated with expression of MGMT, and that MSP may not be well-suited for predicting the prognosis of patients with glioblastoma (15,16).…”
Section: Cpg Site ---------------------------------------------------mentioning
confidence: 99%
“…Temozolomide is an alkylating agent that is increasingly used for relapsed medulloblastoma (20)(21)(22). Although a significant correlation between MGMT methylation status and temozolomide sensitivity has been confirmed in glioblastoma (7,8), sensitivity to temozolomide in relapsed medulloblastoma may not be predicted from the MGMT status of primarily resected tumor samples. Second, the small sample size prevented further analysis of other clinical factors that may be associated with patient outcome, such as molecular subtypes, pathological characteristics, dissemination status and chemotherapy regimens.…”
Section: Cpg Site ---------------------------------------------------mentioning
confidence: 99%
See 1 more Smart Citation